Incidental extensive adenocarcinoma in lungs explanted from a transplant recipient with an idiopathic pulmonary fibrosis flare-up: A clinical dilemma. (2018) - Patil, Pradnya D.; Sultan, Samir; Hahn, M. Frances; Roy, Sreeja Biswas; Ross, Mitchell D.; Abdelrazek, Hesham; Bremner, Ross M.; Thawani, Nitika; Walia, Rajat; Panchabhai, Tanmay S.
Abstract: Patients under consideration for lung transplantation as treatment for end-stage lung diseases such as idiopathic pulmonary fibrosis (IPF) often have risk factors such as a history of smoking or concomitant emphysema, both of which can predispose the patient to lung cancer. In fact, IPF itself increases the risk of lung cancer development by 6.8% to 20%. Solid organ malignancy (non-skin) is an established contraindication for lung transplantation. We encountered a clinical dilemma in a patient who presented with an IPF flare-up and underwent urgent evaluation for lung transplantation. After transplant, the patient's explanted lungs showed extensive adenocarcinoma in situ, with the foci of invasion and metastatic adenocarcinoma in N1-level lymph nodes, as well as usual interstitial pneumonia. Retrospectively, we saw no evidence to suggest malignancy in addition to the IPF flare-up. Clinical diagnostic dilemmas such as this emphasize the need for new noninvasive testing that would facilitate malignancy diagnosis in patients too sick to undergo invasive tissue biopsy for diagnosis. Careful pathological examination of explanted lungs in patients with IPF is critical, as it can majorly influence immunosuppressive regimens, surveillance imaging, and overall prognosis after lung transplant.